Stereoselective syntheses of 3-aminocyclooctanetriols and halocyclooctanetriols - Salamci, Emine; Zozik, Yunus (Beilstein Journal of Organic Chemistry, 2021)
The efficient synthesis of two new stereoisomeric 3-aminocyclooctanetriols and their new halocyclitol derivatives starting from cis,cis-1,3-cyclooctadiene are reported. Reduction of cyclooctene endoperoxide, obtained by photooxygenation of cis,cis-1,3-cyclooctadiene, with zinc yielded a cyclooctene diol followed by acetylation of the hydroxy group, which gave dioldiacetate by OsO4/NMO oxidation. The cyclooctane dioldiacetate prepared was converted to the corresponding cyclic sulfate via the formation of a cyclic sulfite in the presence of catalytic RuO4. The reaction of this cyclic sulfate with a nucleophilic azide followed by the reduction of the azide group provided the target, 3-aminocyclooctanetriol. The second key compound, bromotriol, was prepared by epoxidation of the cyclooctenediol with m-chloroperbenzoic acid followed by hydrolysis with HBr(g) in methanol. Treatment of bromotriol with NaN3 and the reduction of the azide group yielded the other desired 3-aminocyclooctanetriol. Hydrolysis of the epoxides with HCl(g) in methanol gave stereospecifically new chlorocyclooctanetriols.
Keywords: aminocyclitols; aminocyclooctanetriol; chlorocyclooctanetriol; cyclic sulfate; cyclitols

(untitled) - Salamci, E. (Tetrahedron Lett., 2020)

(untitled) - Diaz, L.; Delgado, A. (Curr. Med. Chem., 2010)

(untitled) - Donaldson, W. A. (ARKIVOC, 2018)

(untitled) - Ashry, E. E.; Rashed, N.; Shobier, A. H. S. (Pharmazie, 2000)

(untitled) - Donohoe, T. J.; Flores, A.; Bataille, C. J. R.; Churruca, F. (Angew. Chem., Int. Ed., 2009)
Angew. Chem. 2009, 121, 6629–6632. doi:10.1002/ange.200902840

(untitled) - Griffen, J. A.; White, J. C.; Kociok-Köhn, G.; Lloyd, M. D.; Wells, A.; Arnot, T. C.; Lewis, S. E. (Tetrahedron, 2013)

(untitled) - Ji, L.; Zhang, D.-f.; Zhao, Q.; Hu, S.-m.; Qian, C.; Chen, X.-Z. (Tetrahedron, 2013)

(untitled) - Trapero, A.; González-Bulnes, P.; Butters, T. D.; Llebaria, A. (J. Med. Chem., 2012)

(untitled) - Lo, H.-J.; Chang, Y.-K.; Yan, T.-H. (Org. Lett., 2012)

(untitled) - Ghosal, P.; Shaw, A. K. (J. Org. Chem., 2012)

(untitled) - Aydin, G.; Savran, T.; Aktaş, F.; Baran, A.; Balci, M. (Org. Biomol. Chem., 2013)

(untitled) - Gültekin, M. S.; Salamci, E.; Balci, M. (Carbohydr. Res., 2003)

(untitled) - Salamci, E.; Seçen, H.; Sütbeyaz, Y.; Balci, M. (J. Org. Chem., 1997)

(untitled) - Salamci, E.; Seçen, H.; Sütbeyaz, Y.; Balci, M. (Synth. Commun., 1997)

(untitled) - Seçen, H.; Salamci, E.; Sütbeyaz, Y.; Balci, M. (Synlett, 1993)

(untitled) - Delgado, A. (Eur. J. Org. Chem., 2008)

(untitled) - Chen, X.; Fan, Y.; Zheng, Y.; Shen, Y. (Chem. Rev., 2003)

(untitled) - Kim, J.-S.; Kang, J.-C.; Yoo, G.-H.; Jin, X.; Myeong, I.-S.; Oh, C.-Y.; Ham, W.-H. (Tetrahedron, 2015)

(untitled) - Cantekin, S.; Baran, A.; Çalışkan, R.; Balci, M. (Carbohydr. Res., 2009)

(untitled) - Łysek, R.; Schütz, C.; Favre, S.; O’Sullivan, A. C.; Pillonel, C.; Krülle, T.; Vogel, P. (Bioorg. Med. Chem., 2006)

(untitled) - Harit, V. K.; Ramesh, N. G. (J. Org. Chem., 2016)

(untitled) - Trost, B. M.; Malhotra, S. (Chem. – Eur. J., 2014)

(untitled) - Rajender, A.; Rao, B. V. (Tetrahedron Lett., 2013)

(untitled) - Łysek, R.; Favre, S.; Vogel, P. (Tetrahedron, 2007)

(untitled) - Li, Q. R.; Kim, S. I.; Park, S. J.; Yang, H. R.; Baek, A. R.; Kim, I. S.; Jung, Y. H. (Tetrahedron, 2013)

(untitled) - Ekmekci, Z.; Balci, M. (Eur. J. Org. Chem., 2012)

(untitled) - Shing, T. K. M.; Wong, W. F.; Ikeno, T.; Yamada, T. (Org. Lett., 2007)

(untitled) - Gravier-Pelletier, C.; Maton, W.; Dintinger, T.; Tellier, C.; Le Merrer, Y. (Tetrahedron, 2003)

(untitled) - Karavaizoglu, U. N.; Salamci, E. (New J. Chem., 2020)

(untitled) - Zozik, Y.; Salamci, E.; Kilic, A. (Tetrahedron Lett., 2017)

(untitled) - Ecer, K.; Salamci, E. (Tetrahedron, 2014)

(untitled) - Kaya, A. A.; Salamci, E.; Menzek, A.; Erdem, S. S.; Şahin, E.; Ecer, K. (Tetrahedron, 2017)

(untitled) - Salamci, E. (Tetrahedron, 2010)

(untitled) - Andriuzzi, O.; Gravier-Pelletier, C.; Vogel, P.; Le Merrer, Y. (Tetrahedron, 2005)

(untitled) - Mehta, G.; Mohanrao, R.; Katukojvala, S.; Landais, Y.; Sen, S. (Tetrahedron Lett., 2011)

(untitled) - Andriuzzi, O.; Gravier-Pelletier, C.; Le Merrer, Y. (Tetrahedron Lett., 2004)

(untitled) - Andriuzzi, O.; Gravier-Pelletier, C.; Bertho, G.; Prange, T.; Le Merrer, Y. (Beilstein J. Org. Chem., 2005)

(untitled) - Grabowski, S.; Armbruster, J.; Prinzbach, H. (Tetrahedron Lett., 1997)

(untitled) - Byun, H.-S.; He, L.; Bittman, R. (Tetrahedron, 2000)

(untitled) - Zou, J.; Ni, G.; Tang, J.; Yu, J.; Jiang, L.; Ju, D.; Zhang, F.; Chen, S. (Eur. J. Org. Chem., 2018)